Traditional culinary heritage as a gastronomic tourism product related in Sumbu Filosofi at Yogyakarta - Prasetyanto, Hermawan; Gumelar, Kiki; Nugroho, Setyo Prasiyono; Seth, Muhammad Najib; Susilowati, Heni; Tohari, Amin (Indonesia Research and Study Center, 2026)
This study examines traditional culinary heritage in the Sumbu Filosofi Yogyakarta as a foundation for culture-based gastronomic tourism. A qualitative case study design was applied using observation, semi-structured interviews with culinary practitioners and tourism stakeholders, and document analysis. Data were analyzed through data reduction, data display, and interpretative conclusion drawing. The findings show that culinary heritage in the Sumbu Filosofi area functions not only as a consumptive product but also as a medium conveying Javanese philosophical values and spatial cosmology. Cultural narratives, heritage-based spatial settings, and experiential tourism strengthen gastronomic attractions in urban heritage contexts. This study contributes to heritage tourism and gastronomic studies by positioning culinary heritage as an integral element of philosophical heritage landscapes rather than an isolated tourism commodity. It further demonstrates that sustainable gastronomic tourism in heritage areas requires a contextual development approach that prioritizes cultural value preservation as a core strategy for destination resilience.